DEVELOPING FUNCTIONAL LITERACY OF PRIMARY SCHOOL STUDENTS BASED ON INTELLECTUAL AND CREATIVE SPEECH SKILLS - Измагамбетова, Раиса; OSPANBEKOVA, M.N.; AKHMETOVA, G.H.; NURBEKOVA, S.M.; KOZHAMKULOVA, N.S. (Pedagogy and Psychology, 2025)
In the current education system, students’ functional literacy holds significant importance. It can serve as a tool for developing competencies and activating students’ cognitive activities. The development of a student’s knowledge and competencies is closely linked within a unified learning-cognitive process. One of the aspects of this interconnection is the emphasis in school education on forming students’ functional literacy as a tool for self-development, in accordance with their interests and abilities. The methodological basis of the research is formed by contemporary school education concepts, the main principles of school pedagogy, the theory of developing communicative skills in teaching, the theory of developing students’ functional literacy, and the scientific foundations of communicative education technologies. The sources of the research included state documents on the development of education in Kazakhstan and abroad, scientific works of domestic and foreign scholars on the issue under study, periodicals from Kazakhstan and other countries, materials from scientific-practical conferences, educational programs, and teaching and methodological manuals. During the research, we examined the student’s learning process and the formation of students’ functional literacy within a unified educational-cognitive process. One aspect of this interconnection is the scientific approach in the educational process, where teaching functions as a tool for understanding the surrounding world and as a tool for self-development in accordance with the student’s interests and abilities.